Unobtrusive Cardiac Activity Monitoring Using Biomedical Radar: Principles, Applications, and Perspectives - Yuchen Li; Jie Cao; Qishan Chen; Li Zhang; Changzhan Gu (Bioelectromagnetics in Medicine, 2026)
Background: Continuous cardiac monitoring is important for early cardiovascular risk assessment and long-term health management. Conventional approaches such as electrocardiography, photoplethysmography, seismocardiography, ballistocardiography, and echocardiography provide valuable cardiac information but are limited by body contact, intermittent operation, or user compliance. Millimeter-wave radar offers a contactless electromagnetic sensing approach for detecting subtle body-surface motion related to cardiac activity. This review summarizes recent advances in millimeter-wave radar-based unobtrusive cardiac monitoring, with emphasis on mechanical cardiac waveforms and intra-beat information. Methods: This article is a narrative review of radar-based unobtrusive cardiac monitoring. Representative studies were selected based on their relevance to RF/millimeter-wave cardiac sensing and were categorized by radar architecture, signal-processing method, waveform representation, monitoring scenario, validation modality, and clinical endpoint. Results: Existing studies show that radar can reliably estimate heart rate and heart rate variability under controlled and home-like conditions. Recent work further demonstrates the potential of radar-derived mechanical cardiograms for intra-beat timing analysis, transformation to standard physiological modalities, rhythm classification, blood pressure waveform estimation, and broader cardiac health assessment. Conclusions: Millimeter-wave radar is a promising technology for continuous, contactless cardiac activity monitoring. Future translation requires robust long-term signal extraction, physiological interpretability, standardized datasets, multimodal validation, and clinically meaningful endpoints.